Resection of lesions in the ileum of patients with IgG4-related disease may ameliorate disease progression without steroid administration - Akihiro Watanabe; Takashi Goto; Hitomi Kamo; Ryuji Komine; Naomi Kuroki; Takanobu Sugase; Tsuyoshi Takaya; Rintaro Koga; Hiroshi Hojo; Shoji Taniguchi; Kazuhiko Ibusuki; Kazumi Koga (Surgical Case Reports, 2018)
Abstract Background IgG4-related disease (IgG4-RD) is a pathological condition that is characterized by an infiltrate composed of IgG4-positive plasma cells and recently recognized as an immune-mediated condition. It causes tissue throughout the body to become stiff and thickened due to autoimmune reactions that cause fibrosis and scarring. Disease-related changes commonly occur in the salivary glands, bile duct, pancreas, and lungs, but are seldom seen in the small bowel. A diagnosis of IgG4-RD is suspected if a high level of IgG4 is found on a blood test. The ideal diagnostic method is pathological examination, but because the clinical manifestations of IgG4-RD are very diverse and nonspecific, the disease may often go undiagnosed until an unrelated biopsy or resection specimen is obtained. The most common treatment for IgG4-RD is steroid use. However, tapering or stopping steroid administration is seen to result in recurrence in approximately 50% of cases. A complete cure is therefore considered extremely difficult. Case presentation A 69-year-old man with gastrointestinal obstruction underwent small bowel resection for two lesions. On histopathological examination, the specimen showed features of IgG4-RD. We performed several tests to detect other characteristics of IgG4-RD, but were unable to find any. The patient is being followed up regularly for a year and is being observed for any symptoms of recurrence. Conclusions We present a case of IgG4-RD wherein the ileum wall was significantly sclerosed, leading to gastrointestinal tract obstruction; therefore, we resected two sections of the ileum. We believe that resection of IgG4-RD lesions can help avoid long-term steroid use in patients, because the surgery completely eliminates the pathological origins of the condition.